2014
DOI: 10.1097/mpg.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of the Glucagon‐Like Peptide 2 Analogue, Teduglutide, on Intestinal Adaptation in Short Bowel Syndrome

Abstract: Neonatal short bowel syndrome following massive gut resection is associated with malabsorption of nutrients. The intestinotrophic factor glucagon-like peptide 2 (GLP-2) improves gut function in adult patients with short bowel syndrome, but its effect in pediatric patients remains unknown. Our objective was to test the efficacy of the long-acting synthetic human GLP-2 analogue, teduglutide (ALX-0600), in a neonatal piglet jejunostomy model. Two-day-old pigs were subjected to resection of 50% of the small intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 29 publications
(51 reference statements)
2
47
1
Order By: Relevance
“…In parameters such as normalized intestinal weight, mucosal weight, and villus height, there was no difference between combination therapy and GLP-2 alone, but both treatments were superior to saline control and/or EGF-cm alone. This suggests that GLP-2 is the main factor stimulating increases in these parameters, consistent with prior studies demonstrating that GLP-2 administration in rodents and piglets expands the intestinal mucosal epithelium (13,28,30,37,40,42,44). However, EGF-cm alone appeared to be selectively beneficial in increasing bowel weight per length and jejunal villus height in the JI group only.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In parameters such as normalized intestinal weight, mucosal weight, and villus height, there was no difference between combination therapy and GLP-2 alone, but both treatments were superior to saline control and/or EGF-cm alone. This suggests that GLP-2 is the main factor stimulating increases in these parameters, consistent with prior studies demonstrating that GLP-2 administration in rodents and piglets expands the intestinal mucosal epithelium (13,28,30,37,40,42,44). However, EGF-cm alone appeared to be selectively beneficial in increasing bowel weight per length and jejunal villus height in the JI group only.…”
Section: Discussionsupporting
confidence: 90%
“…Given that remnant anatomy is a significant predictor of pathophysiology and outcome in SBS, we therefore developed two neonatal piglet SBS models, one with midintestinal resection and another with distal intestinal resection (25). GLP-2 or teduglutide administration for 7 or 14 days in neonatal piglet SBS models stimulates structural adaptation, including increases in remnant villus height and crypt depth, but has limited or transient functional effects on digestive enzyme activity or nutrient transport (30,40,42,44).…”
mentioning
confidence: 99%
“…Exogenous GLP-2 administration stimulates intestinal growth and disaccharidase activities in TPN-fed preterm pigs with or without intestinal resection (37,49,51). Preterm piglets normally show increased basal circulating levels of GLP-2, compared with pigs born at term, indicating a role for GLP-2 in the maturational process around birth (38).…”
Section: Discussionmentioning
confidence: 99%
“…Petersen et al (2001) demonstrated that the enzymes sucraseisomaltase and lactase-phloridzin hydrolase were unaffected by GLP-2 in late-gestation foetal and parenterally fed neonatal piglets when GLP-2 (12.5 nmol/kg) was administered twice daily for 6 days. In another study, newborn total parenteral nutrition-fed pigs were subjected to daily single administration of teduglutide for 7 days; as a result, small bowel growth was increased and minimal effect was elicited on digestive enzyme expression or nutrient absorption (Thymann et al, 2014a). However, GLP-2 treatment resulted in adverse outcomes, including decreased tissue maltase and sucrose in both sham and small bowel resection piglets (Pereira-Fantini et al, 2008).…”
Section: Digestive Functionmentioning
confidence: 99%